Application of mind mapping-based health education in perioperative nursing of glioma patients undergoing awake surgery (基于思维导图的宣教模式在脑胶质瘤患者唤醒手术围手术期中的应用效果) - ZHANG Fuli (张富丽); ZHONG Liyun (仲丽芸); DENG Lan (邓岚); ZHANG Aifang (张爱芳); SHANG Wuyi (尚无怡) (中西医结合护理, 2023)
To evaluate the mind mapping-based health education in perioperative nursing of glioma patients undergoing awake surgery. Methods Totally 60 glioma patients undergoing awake surgery were randomly divided into the intervention group and control group, with 30 cases in each group. The control group received routine perioperative nursing and health education, and the intervention group was given mapping-based health education in addition to routine nursing. The patient satisfaction, readiness for hospital discharge and anxiety state were measured and compared between two groups. Results Score of Hamilton Anxiety Scale(HAMA) in the intervention group was lower than that in the control group (P＜0. 05). Score of Readiness for Hospital Discharge Scale(RHDS) in the intervention group was higher than that in the control group (P＜0. 05). The score of patient satisfaction assessment in the intervention group was higher than that in the control group (P＜0. 05). Conclusion The mind mapping-based health education is potentially effective to improve the patient satisfaction and preparedness for discharge, and relieve the anxiety of glioma patients undergoing awake surgery. (目的 探讨基于思维导图的宣教模式在脑胶质瘤患者唤醒手术围手术期中的应用效果。方法 选取首都医科大学附属北京天坛医院2021年3月—12月收治的拟行术中唤醒的脑胶质瘤患者作为研究对象, 随机分为对照组(n=30)和干预组(n=30)。对照组接受常规围手术期护理和健康教育, 干预组在对照组的基础上接受思维导图的健康宣教模式。对比两组患者满意度、出院准备度和焦虑情绪。结果 干预组患者HAMA量表评分低于对照组, 差异有统计学意义(P＜0. 05); 干预组RHDS量表总分高于对照组, 差异有统计学意义(P＜0. 05); 干预组满意度评分高于对照组, 差异有统计学意义(P＜0. 05)。结论 基于思维导图的健康宣教模式能有效提高脑胶质瘤患者满意度和出院准备度, 缓解患者焦虑情绪。)